Effective judicial protection in judicial cooperation in civil matters and the Court of Justice of the European Union case law: the public policy clause and the absolute default of appearance as denial causes of judgments' recognition and enforcement in EU context - Abreu, Joana Rita Sousa Covelo (2014)
The Brussels I Regulation’s re-foundation by the New Brussels I Regulation was thought to secure reciprocal trust on justice administration among Member States and to grant full access to justice for those who inhabit and circulate in its territory. In a Union characterized by circulation freedoms and an internal market existence, those principles justify a situation in which judgments ruled by a Member State’s court are automatically recognised and enforced, in other Member-State, except when the defendant evokes the rules on denial of judgments’ recognition and enforcement. There would not be judicial cooperation and integration’s prosecution without trust – trust must exist among Member States’ courts and it must be felt by EU citizens so they can acknowledge that EU is actively seeking to improve their life and working conditions. The European Commission made constructive efforts to promote an exequatur’s abolition, making recognition and enforcement proceedings on the New Brussels I Regulation simpler (it even proposed to remove the “public policy” clause, which was not accepted). It is necessary to analyse how the CJEU applies the rules on denial of judgments’ recognition and enforcement to perceive if the principle of an effective judicial protection is fulfilled under New Brussels I Regulation.